Translational regulation of human papillomavirus mRNAs in carcinogenesis: old questions and new insights - Baranda-Ávila, Noemi; Maldonado, Giovanna; Vélez, Dora E.; Hernández, Greco (Frontiers in Cell and Developmental Biology, 2025)
Persistent infection with high-risk human papillomaviruses (HR-HPVs) is a major etiological factor in the development of cervical cancer, which ranks as the fourth leading cause of cancer-related mortality among women worldwide. HR HPV types 16 and 18 cause more than 70% of all cases. These viruses encode the proteins E1, E2, E1^E4, E4, E5, E6, E7, L1, and L2, through a complex array of polycistronic mRNAs. For decades, research on HPV gene expression has focused predominantly on transcriptional activity and mRNA splicing. In contrast, the mechanisms underlying the translation of mRNAs remain poorly understood. Whereas the translational regulation of E1, E2, E6, and E7 has been elucidated, the translation mechanisms for E5, L1, and, L2 proteins are still unclear. We hypothesized that their translation may occur via internal ribosome entry sites (IRESs). Other critical questions also remain open, including how the viral-cellular chimeric transcripts generated upon virus genome integration into the host DNA are translated, as well as how the translation of polycistronic viral mRNAs is regulated during the differentiation of epithelial cells—a process that is central to HPV-induced carcinogenesis. This review summarizes current knowledge showing that the translation of HPVs mRNAs is subjected to tight regulation, highlights unresolved questions, and discusses potential therapeutic implications of targeting the translational machinery in HPV-related cancers.